A systematic review on the use of serious games in project management education - Magnus M. Hellström; Dominique Jaccard; Knut Erik Bonnier (Serious Games Society, 2023)
Project management education is well suited for active learning through serious games, and a lot of research has been published on the use of serious games for project management education. Earlier reviews have focused on the content and features of project management serious games. The objectives for using those serious games have been less reviewed. The aim of this study was to conduct a systematic review to better understand the objectives of using serious games in project management education, with the following research question: Why are project management serious games used in higher education? A systematic review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A systematic search enabled us to identify 175 articles, of which forty-three met the eligibility criteria. An inductive content analysis of those articles showed that project management serious games are used mainly for pedagogical and practical reasons. From a pedagogical perspective, serious games are mainly used to develop specific skills that are difficult to acquire in classic ex cathedra lectures, such as practical competencies and soft skills. From a practical perspective, serious games are mainly used for proposing a risk-free trial environment. Based on our analysis, we propose a taxonomy of reasons for using PM games in higher education. Our study also reveals that few studies assess whether serious games meet all their objectives, and that more research is needed on how to implement them into a coherent pedagogical scenario.